Cfd simulation of swirling in fluidized bed by using annular type distributor - Mohd Nor Aidil, Mohd Azlan (2013)
This paper report about the swirling fluidized bed (SFB) which is affected by the designs of perforated plate. The result of the flow simulation for the each distributor plate perforated, inclines and annular are produces by using the Solid Work Flow Simulation intuitive (CFD). The characteristic of the each design plate are different in their number of hole, diameter of hole, thickness of plate and diameter of plate in order to get the best result which respect to pressure drop. The performance of the SFB was assessed in term of pressure drop values, minimum fluidization velocity, Umf. Also the performance of the each plate are looked at their flow air pattern in fluidized bed, which are the more swirl pattern of air the more better in result. More importantly is the reduction pressure drop in the appropriate design in distributor plate. The good results in this study were produced by the annular plate which is able to produce a minimum pressure drop compared with the perforated and Incline plate. While the annular plate also shown the swirl of air pattern better than perforated and incline plate. Furthermore, to ensure better results in this study, the experiment shall be conducted so that the results of the experiment can be compared with the flow simulation results. Besides that, from the experiment also the results that produce have more actual compare with flow simulation result.